Keanekaragaman Makrozoobentos sebagai Bioindikator Kualitas Perairan Ranu Pani-Ranu Regulo di Taman Nasional Bromo Tengger Semeru - Gazali, Achmad (Prosiding KPSDA, 2015)
Ranu Pani and Ranu Regulo (2,200 masl) are lakesin Bromo Tengger Semeru National Park (TN.BTS) by area 1 ha and 0.7 5ha. Lakes were used for tourism,agriculture, live stock and fishing spot. Civil and visitorsÂ activities give an effect onwater quality. The study was conducted in February-June2011, the aim of study to determine the diversity of macrozoobenthos, to know the water quality by seen thebioindicators and physico-chemical factors. Samples were taken at each of the five observation stations by Ekman Dredge and by hand. Samples were identified and analyzed by Shannon â Winner diversity (H) and Simpson dominance(D) indices. The results of study in Ranupani were consisted by 93 of Bulimidae, 14 of Hirudidae, 22 of Glossiphoniidae, 1 of Syrphidae, 1 of Gomphidae, 1 of Gammaridae and 3 of Coanagrionidae The results in RanureguloÂ were consisted by50 of Coanagrionidae,5 of Asselidae and 5 of Aeshnidae. The diversity indices was higher in RanuPani (0,98) than Ranuregulo (0.57). The dominance in deces was lower in Ranu Pani (0.51) than Ranu Regulo (0.71). Water conditions based on bioindicatorÂ in Ranu Pani were classified as medium pollutedâpolluted.Water conditions in Ranu Regulo were polluted. The condition both ofwatersbased onH was weight polluted. The analysis ofphysico-chemical factors (based on PP.No.82.year.2001 onWater Quality Standards) for measuringof pH, DO, BOD, COD, nitrate, TSS andÂ TDS showed that the watersin Ranu Pani and Ranu Regulo included to class II and III(except Hatstation IV Ranu Regulo included to class IV and TSS at station II, IV, V waters Ranu Pani feasible for classIII). The Phosphate analysis showed that both of waters included to class III.